Lovely tupperware: The role of brand love in mediating brand loyalty - Nugraha, Kristian Suhartadi Widi (Universitas Bangka Belitung, 2024)
This research aims to determine the effect of brand personality and emotional brand attachment on brand love and brand loyalty in Tupperware products in the city of Jember. Respondents in this research amounted to 170 with the purposive sampling method carried out using a hybrid—analysis using SEM-PLS with data processing using SmartPLS version 3. The results showed that brand personality has a significant effect on brand love and also brand loyalty. Likewise, emotional brand attachment has a significant effect on brand love and brand loyalty. Related to the mediation function, brand love is successful and critical in building brand loyalty. The managerial implication in this study is to make brand love a proxy in the company's brand strategy as well as a bridge to maintaining loyalty